Wireless traffic light controller - Thatsanavipas, K.; Ponganunchoke, N.; Mitatha, S.; Vongchumyen, C. (My University, 2011)
We propose a new system for wireless traffic light controller, it makes a traffic policeman easily and effective control a roadjunction with a wireless remote control. The system has two modes, Manual and Automatic. Manual mode provide the control oftraffic light to change manually by the traffic policeman, by just press the button related to the direction of the street to make agreen light signal. The remote will respond by checking the bearing of the pressed button on the remote using Hall effects sensorregarding to the position and direction of the remote. Then send the control signal to the traffic light controller board. Inautomatic mode, the traffic light controller board will change the light sequence according to the preset patterns and time delay,the traffic policeman be able to change the pattern at any time using the remote. The propose system help the policeman tocontrol the junction by himself and be able to change conditions of the traffic flow dynamically.
Keywords: Hall Effect; Remote control; RF transmission; Traffic light controller; Wireless control